2022
DOI: 10.1001/jamanetworkopen.2022.25485
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Patient-Reported Symptoms and Adherence to Adjuvant Endocrine Therapy Among Women With Early-Stage, Hormone Receptor–Positive Breast Cancer

Abstract: This cohort study evaluates the differences in patient-reported symptoms and adherence to adjuvant endocrine therapy by race among women with early-stage breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Interestingly, Black patients reported worse QOL with HT compared to White patients. Schleinitz et al and Hu et al, [ 16 , 35 ] reported the similar results as ours showing that Black women noted lower quality of life with HT during breast cancer treatments.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, Black patients reported worse QOL with HT compared to White patients. Schleinitz et al and Hu et al, [ 16 , 35 ] reported the similar results as ours showing that Black women noted lower quality of life with HT during breast cancer treatments.…”
Section: Discussionsupporting
confidence: 88%
“…There is limited data regarding the gynecologic outcomes of Black breast cancer survivors on tamoxifen. One particular retrospective cohort study investigated symptom burden by race and its relationship to endocrine therapy adherence [ 59 ]. Using data from a large multidisciplinary cancer center, researchers used 9 major symptom clusters, one of which was gynecologic symptoms.…”
Section: Tamoxifen Usementioning
confidence: 99%
“…Previous studies on other types of malignancies have demonstrated worse compliance with adjunctive therapy and poorer clinical outcomes among pediatric patients with SDOH disparities. 28,29 Univariate Analysis of Disparities in SDOH, Outcomes, and Follow-up…”
Section: Patient Demographicsmentioning
confidence: 99%